A Conceptual Study of Electronic Tax Filing Adoption - Dr. Dharmendra Thaker (Research Parks Publishers, 2022)
This paper attempts to develop an understanding about tax system and e-filing adoption which is mandatory to all individual tax payers. The objectives of e-filing are to facilitate tax compliance and to provide taxpayers service through the use of internet technologies and WWW. Electronic filing systems have been very successful in filing the (ITR) income tax return. The effectiveness and efficiency of the income tax return will only be enhanced as these systems are implemented. Filing of Income Tax returns is a legal obligation of every person whose total income for the previous year has exceeded the maximum amount that is not chargeable for income tax under the provisions of the (ITA) Income Tax Act, 1961. Income Tax Department has introduced a convenient way to file these returns online using the Internet. This attempt to develop an understanding about how to make e- filing by all citizens of India.